Strategi meningkatkan kualitas dan semangat santriwati dalam berbahasa Arab melalui berbagai metode pembelajaran bahasa Arab di Pondok Pesantren Putri Salafiyah Kauman Bangil - Udzma, Nurissyafa'atil (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2025)
Arabic language learning is essentially designed to master the four language skills: listening, speaking, reading, and writing. To achieve the goals of Arabic language learning, teachers must be able to apply appropriate and innovative methods and methods for their students, whether in Islamic boarding schools, madrasas, or even schools, to improve students' Arabic language skills. Madrasas can also assist teachers who want to innovate in learning by providing opportunities for teachers to use various learning approaches. This study aims to describe efforts to improve the quality and enthusiasm of female students in Arabic language learning through various methods. This research method uses qualitative research. Because it obtains ready-to-use data collected by other parties using various methods or methods that can help describe an object accurately, clearly, and comprehensively. The results of the study indicate that the forms of programs in Salafiyah Islamic boarding schools, both weekly, monthly, and annually, starting from the beginning to the final grade, are very effective in improving the quality and enthusiasm of female students in Arabic. All language elements are combined and then integrated into Arabic language learning, such as grammar, sharraf, qowaid, translation, and so on. The conclusion of this study is that all grade levels are taught Arabic in Salafiyah Islamic boarding schools, from the beginning to the end of the class. Each class or level has its own learning characteristics, because Arabic is taught in stages and levels, while the all-in-one learning system combines all language elements such as grammar, sharraf, qowaid, translation, and so on. The teaching method of the Arabic language learning model above is based on each level. The teaching materials used also vary depending on the situation and condition of the students, and the teaching methods also vary depending on the teaching materials used. The learning system above helps anyone who wants to learn the language from the beginning or beginner level to the final level.